HUMANISASI FIKIH DALAM FENOMENA â€œAZAN TOLERANâ€ PADA MASYARAKAT TANI TEMANGGUNG - Nashihin, Husna (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2019)
This field research uses the phenomenology approach. Islam as a moderate, humanist, and rahmatan lil amin alamin religion must be able to solve the increasing of complexity problems. This complexity can be found in the phenomenon of delaying the time of praying together in farming community of Temanggung which is be great debate in the middle community of Temanggung. The phenomenon of delaying the time of praying together in farming community of Temanggung cannot be solved just using the Fikih approach. Humanization of Fikih is urgent to be done in solving this problem, so Islam can be a solution to the community problems in Temanggung. Based on the Ijmaâ€™ Ulama, Fikih require the implementation of Azan and praying together on time, although this opinion still becomes an ikhtilaf. Based on sample of 27 mosques which were the object of this research, there are two models of delaying the time of praying together in farming community of Temanggung, namely; first, the model of delaying the time of praying Dhuhur and Ashar together. Second, the model of delaying the time of praying Ashar together. The reason for the delaying the time of praying together in farming community of Temanggung is related with factor of working. Agricultural working does not allow imam, muazin and majority men to carry out the Syariâ€™at. Furthermore, this causing raises an agreement of delaying the time of praying together in farming community of Temanggung. Fikih humanization is carried out using a socio-economic approach, so Fikih can be accepted by Temanggung's farming community.